2002
DOI: 10.1897/1551-5028(2002)021<2080:daaoao>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an Oil Toxicity and Exposure Model, Oiltoxex

Abstract: An oil toxicity and exposure model (OilToxEx) was developed and validated for estimation of impacts to aquatic organisms resulting from acute exposure to spilled oil. Because oil exposure is shorter than the time required for equilibrium between the organism and the water to be reached, the time and temperature dependence of toxicity is addressed. Oil toxicity is a function of aromatic composition and the toxicity of individual aromatics in the mixture. Lethal concentration to 50% of exposed organisms (LC50), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 66 publications
2
68
0
Order By: Relevance
“…From Figure 1, it may be seen that LC50 t varies very little for more than 24 h of exposure for these chemicals (C1‐naphthalene has log[ K ow ] = 3.87). Regressions on the available data sets indicate significant negative slopes, consistent with model predictions [74]. However, data are insufficient to statistically verify the Spacie—Hamelink equation with this data set.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…From Figure 1, it may be seen that LC50 t varies very little for more than 24 h of exposure for these chemicals (C1‐naphthalene has log[ K ow ] = 3.87). Regressions on the available data sets indicate significant negative slopes, consistent with model predictions [74]. However, data are insufficient to statistically verify the Spacie—Hamelink equation with this data set.…”
Section: Resultssupporting
confidence: 59%
“…A total of 278 MAH and PAH LC50 estimates were obtained from the literature, 115 for fish, 129 for crustaceans, and the remainder (34) for other invertebrates [74]. Forty‐one species are represented in the data set.…”
Section: Resultsmentioning
confidence: 99%
“…This is an important observation, because often, only the aromatic component, specifically BTEX, is considered when assessing aquatic toxicity hazards from gasoline. The situation is similar for oils, in which dissolved aromatics are believed to be the main components responsible for toxicity [36]. Barron et al [37] demonstrated that PAHs were not the majority determinant for the toxicity of three middle‐distillate oils to mysid shrimp in laboratory tests.…”
Section: Resultsmentioning
confidence: 99%
“…Toxicity testing data from laboratory studies have facilitated our understanding of the effects of oil and oil constituents on a diverse number of aquatic species. This information has been reviewed by the US National Academy of Sciences, the American Petroleum Institute, the National Oceanic and Atmospheric Administration, and other institutions and scientists facilitating the development of useful benchmarks that help inform decision makers . However, shortcomings are inherent in the use of standard laboratory toxicity data to assess the effects to water column biota from chemically treated oil spills, as well as to support management decisions on the offshore use of dispersants.…”
Section: Introductionmentioning
confidence: 99%